Computational fluid dynamics study of hydrogen production by sorption enhanced steam ethanol reforming process in fluidized bed. (15th July 2023) - Yu, Hongshi; Sun, Haoran; Bao, Guirong; Liu, Huili; Hu, Jianhang; Wang, Hua
Highlights: Sorption enhanced steam ethanol reforming for hydrogen production simulated. Relationships between key parameters of particles analyzed. Enlarging steam flow rate promotes the yields of hydrogen and carbon dioxide. Particles in dense region have large temperature and small heat transfer coefficient. Abstract: As a renewable resource, hydrogen plays a pivotal role in the energy transition of the current world. A promising route for hydrogen production is the sorption enhanced steam ethanol reforming (SE-SER), which is characterized by the complex multi-scale characteristics. This paper aims to explore the hydrodynamic (e.g., gas and solid flux, solid dispersion and velocity) and thermodynamic (e.g., particle temperature and heat transfer coefficient) characteristics on the micro-level together with the effect of operating parameters on the SE-SER performance. Accordingly, the reactive multiphase particle-in-cell (MP-PIC) model has been developed under the Lagrangian manner for studying the SE-SER process in the bubbling fluidized bed. In this model, it is assumed that uniform temperature appears inside the particle, and particles with similar properties are packed into a parcel to reduce computational cost. This model has been well validated with experimental data. The results indicate that along the bed height, the solid temperature decreases while the heat transfer coefficient increases. H2 and CO2 have similar distribution in the bed, mainly accumulating in the upper part of the reactor. Enlarging the ratio of H2 O to C2 H6 O in the gas mixture promotes the yields of H2 and CO2 . The relationships between key particle variables are explored. It is found that increasing the slip velocity enlarges the particle heat transfer coefficient, and large particle Reynolds number mainly appears with small solid volume fraction. The explored results provide valuable insights into deeply understanding complex multiphase flow and optimizing actual operation of the SE-SER field.